The Effect of Personal Protective Equipment Uptake on the Risk of Leprosy in Adults: Meta Analysis - Rizki Kurniawan Saputra; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Leptospirosis is an acute infectious disease that can attack humans and animals caused by the Leptospira bacteria. Leptospirosis contributes to morbidity and mortality in the high-risk group, namely adults. Compliance with the use of personal protective equipment and direct contact with animal tissue infected with Leptospira sp. bacteria increase the risk of leptospirosis. This study aims to analyze the magnitude of the effect of using personal protective equipment on the risk of leptospirosis with a meta-analysis.Subjects and Method: This was a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles is through a journal database which includes: PubMed, Springer Link, Google Scholar and Science Direct by selecting articles published in 1999-2020. Keywords used